Gap Analysis of Good Manufacturing Practices for The Household Industry (CPPB-IRT) Implementation at MN Sambal MSMEs, Bogor - Ai Fatimah; Rahmi Sonya Putri; Mrr. Lukie Trianawati (Batrisya Education, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in the food sector play a crucial role in supporting food security and local economic growth. A common challenge faced by these businesses is the lack of implementation of Good Manufacturing Practices for Household Industry (CPPB-IRT) that This hinders their ability to obtain the SPP-IRT (Household Industry Food Production Certificate), which is essential for ensuring food safety and quality. MN Sambal, an MSME producing chili sauce as a food product susceptible to spoilage and poses a significant risk to consumers if not handled properly. To assess MN Sambal's compliance with CPPB-IRT standards, research data was collected through observation, interviews, checklists, and literature review. The gap analysis based on BPOM regulation No. HK.03.1.23.04.12.2206 2012 revealed that MN Sambal achieved a high level of compliance are 83.8% conformity aspect and 16.2% non-conformity aspect. These non-conformities were identified in six aspects: Hygiene and Sanitation Facilities and Activities, Process Control, Food Labelling, Supervision by Responsible Parties, and Employee Training. Based on these nonconformities, it is recommended that MN Sambal undertake corrective actions to enhance CPPB-IRT implementation and increase its chances of obtaining the SPP-IRT certification, which will ultimately lead to increased product value and market expansion.